The Classification and Design of New Tensegrity Structure Based on the Area Coverage Concept - Malai, Visuwat; Joneurairatana, Eakachat; Sirivesmas, Veerawat (วารสารสันติศึกษาปริทรรศน์ มจร, 2024)
This research was conducted to explore, classify and propose design principles for new types of tensegrity structures for area cover applications. Tensegrity structures are widely used in the fields of engineering and architecture to create bridges, domes, and buildings because the structures are flexible, lightweight and can be expanded into a variety of forms. Moreover, the tensegrity structure had a series of continuous cables in tension and another set of discontinuous struts in compression. It was usually flexible, lightweight, and capable of spanning wide ranges but considered complex and challenging to assemble. This practical research involves the classification, development of models, and their application to specific types of work. The research process is divided into six main steps: Classification, Summary, Hypotheses, Experiments, Results, and Deliveries. Experiments with physical models are also conducted to explore potential variations in tensegrity structures. This method helps verify forces, identify form-finding factors, and create efficient designs. The results of this research can be used to guide the development of architecture, product design, and other designs by leveraging the classifications, principles, and methods established in this study. In addition, the research and experimentation process involve an in-depth exploration of the structural forms and properties of each type, leading to the creation of new designs and the ability to apply each structure according to its intended use. The development of such structures introduces numerous possibilities for comprehending Tensegrity structures and acts as a catalyst for advancements across various applications. The primary focus is on investigating the origins and historical evolution of Tensegrity structures, highlighting their advantages and disadvantages. Additionally, the research aims to classify existing types and propose a new Tensegrity structure with controllable width and length expansion. The overarching goal is to provide a comprehensive understanding, facilitate practical applications, and extend the design capabilities of Tensegrity structures.